Isolated right ventricular hypoplasia caused by giant aneurysm of right coronary artery to left ventricle fistula in an adult: a case report. Issue 1 (December 2016) - Zhu, Fawang; Zheng, Zhelan; Yao, Lei; Mou, Yun; Cheng, Yan; Gao, Huanhuan
Abstract Background Right ventricular hypoplasia (RVH) is often caused by tricuspid valve atresia and pulmonary valve atresia. this condition leads to low right ventricular blood volume and right ventricular maldevelopment. But, in adults, the main cause of RVH may also be associated with alloplasia of the right coronary artery, which results in an insufficient blood supply to the right ventricular myocardium. Isolated RVH caused by a right coronary artery fistula is very rare and requires immediate treatment. Case presentation We herein report a case involving a 45-year-old man who presented with isolated RVH caused by a giant aneurysm from the right coronary artery to a left ventricle fistula. Echocardiography showed that the right coronary artery was extremely tortuous and obviously dilated with a huge aneurysm. A fistula drained from the right coronary artery into the left ventricle. Moreover, the right heart chamber was significantly collapsed due to extrinsic compression of multiple tortuous, dilated vascular structures. The patient was referred to cardiac surgery. The giant aneurysm was resected, and the proximal and distal openings were closed directly. The fistula was also closed directly, and bypasses were constructed sequentially from the ascending aorta to three branches of the right coronary artery. Conclusions Although standard therapeutic strategies of isolated RVH secondary to a right coronary artery fistula are not well established because of the rarity of this condition, our clinical results show that diagnostic echocardiography, coronary artery angiography, and cardiac computed tomography angiography followed by surgical treatment may be an effective management option.